On the generalized Gauss hypergeometric function - N. A. Virchenko (Vestnik Samarskogo gosudarstvennogo tehničeskogo universiteta. Seriâ Fiziko-matematičeskie nauki, 2008)
In this work the (τ, β)-hypergeometric Gauss function is considered, the basic properties of this function are investigated, some applications are given.